(untitled) (Eurasian Journal of Philology Science and Education, 2025)
This article explores the significance of Akhmet Baitursynuly’s theory of “Living Knowledge” in the context of understanding the interconnectedness of the Human and the Universe, as well as its cognitive-pedagogical potential within the modern educational paradigm. The concepts of “essential knowledge” and “methodical knowledge,” introduced in the framework of this theory, represent key categories in the spiritual and intellectual development of the individual. Based on these concepts, the inseparable link between knowledge, life, human inner being, and the nature of cognition is revealed, underscoring the necessity of their integration with contemporary scientific paradigms. The theoretical foundations laid by Akhmet Baitursynuly are correlated with fundamental ideas from the fields of astrophysics, neurobiology, and quantum physics, as advanced by scholars such as S. Hawking, R. Feynman, and E. Frank. Building on this framework, the paper examines the practical implementation of Baitursynuly’s theory within today’s educational systems, particularly in the teaching of the Kazakh language as a mother tongue. It further addresses the views of international researchers regarding the concept of “Living Knowledge,” drawing connections to the philosophical ideas of Abai Kunanbayev and Al-Farabi within the triadic model of “Teaching – Science – Knowledge.” The primary aim of the study is to reconceptualize the content of the “Living Knowledge” theory in light of current scientific paradigms, while also identifying its epistemological potential for fostering a holistic understanding of the relationship between humans and the universe. Additionally, the paper proposes scientific and methodological foundations for effectively applying this theory in education, especially in teaching the Kazakh language as a native tongue. The study concludes that Akhmet Baitursynuly’s “Living Knowledge” theory should not be viewed solely as a historical legacy, but rather as a conceptual framework that underpins the philosophical, psychological, and methodological foundations of modern education. Keywords: education system, “Living Knowledge” theory, modern science, worldview, “essential knowledge,” “methodical knowledge.”